ANALISIS PENGARUH KUALITAS PRODUK, HARGA DAN PERSONAL SELLING TERHADAP KEPUTUSAN PEMBELIAN PRODUK SPRING BED EVERISE PADA PD. SINAR KOTA - B31111023, Albertus (Jurnal Manajemen Update, 2017)
The development of the world currently running rapidly, thus creating an increasingly tight business competition. By karna that PD. Sinar Kota saw opportunities with market products namely spring bed Everise. Spring bed Everise is already currently demand by consumers in meeting the needs of the bed. This study aimed to analyze the effect of product quality, price and personal selling on purchase decisions in PD. Sinar Kota. Quantitative research causal form. The population in this study is the consumer in PD. Sinar Kota and who have made a purchase of at least two times. This study using purposive sampling, sample in this study of 100 people. The data analysis used is multiple linear regression. Analysis techniques are used i.e. multiple linear regression analysis using SPSS program version 16.0. The results of the analysis of the data obtained simultaneously shows that product quality, price and personal selling effect significantly to purchasing decisions, with a value of significance 0.000. Partially the quality products (0.395) and personal selling (0.666) influential positive (unidirectional) against the decision of the purchase price, but the negative effect (no unidirectional) as seen from table T with a value of Beta (-0.146) against the decision of the purchase. Adjusted R Square value of 91,2%, the balance while of 8,8% is another factor is not scrutinized in this study. keywords: product quality, Pricing, personal selling, purchasing decisions